The Oxford companion to fairy tales - Zipes, Jack 1937- (Oxford ; New York : Oxford University Press, 2000)
"Researchers from scholars to the general public will find this reference source an excellent starting place to find definitions, summaries, authors, artists, and regional and historical overviews of fairy tales, past and present."--"Outstanding Reference Sources," American Libraries, May 2001.
Includes bibliographical references (p. [563]-601).
Keywords: Fairy tales -- History and criticism